Influence of components of anesthesia on dynamics of stress markers in gynecological laparoscopic surgery. - V. Khalimonchyk; O. Klygunenko (Medičnì Perspektivi)
Surgical procedures are associated with a complexity of stress response characterized by neurohumoral, immulogic, and metabolic alterations. Objective: to evaluate the effect of combined intraoperative use of ketamine in low subnarcotic doses and dexketoprofen on intensity of the pain syndrome and dynamics of the stress response in gynecological laparoscopic surgery. A total of 45 patients scheduled for laparoscopic gynecological surgery under total intravenous anesthesia (TIA) were examined randomly and divided into 2 groups. Demographic characteristics, anthropometric data, functional status, duration of surgery and anesthesia were similar in all groups. Group 1 (n=25) patients received total intravenous anesthesia (TIVA) with propofol and fentanyl. Group 2 (n=20) patients received TIVA with additional administration of subanesthetic doses of ketamine and a single administration of 50 mg of dexketoprofen 30 minutes before the end of the surgery. Cortisol and blood glucose levels were evaluated before induction into anesthesia, after the main stage of operation, 2 and 24 hours after surgery. The intensity of postoperative pain was evaluated by VAS in 2 and 24 hours after surgery. The intensity of postoperative pain, concentration of serum cortisol 2 hours after surgery were significantly lower (p <0.05) in patients of group 2, compared to control (p<0,05). Differences of blood glucose levels between groups at the stages of the study were not identified. Combined intraoperative use of subanesthetic doses of ketamine and dexketoprofen at the end of the surgery provides a stress-protective effect. This is confirmed by the rapid normalization of serum cortisol levels and stable blood glucose levels after surgery and is manifested by a low level of postoperative pain syndrome.